Analysis of Factors that Have A Role in Improving Quality of Nursing Services in Inpatient Care - Neti Rusmilaningrum; Harif Fadhillah; Eni Widiastuti; Muhammad Hadi (GLOBAL HEALTH SCIENCE GROUP, 2026)
The quality of nursing care is a crucial aspect of the global health system, as nurses comprise the largest health workforce and are on the front lines of patient care. The quality of nursing care in hospitals is also influenced by several factors, such as leadership, organizational culture, burnout, and work motivation..This research aims to identify factors (leadership, organizational culture, burnout and motivation) that play a role in improving the quality of nursing services in the Inpatient Ward of Jakarta Harbor Hospital. The method used was a quantitative analytical research design with a cross-sectional approach. The research sample consisted of 100 health workers selected using total sampling techniques. The research sample consisted of 100 health workers selected using a total sampling technique. The dependent variable was the quality of nursing services, while the independent variables were leadership, organizational culture, burnout, and motivation. The research instruments used in this study had been tested for validity and reliability prior to data collection. The validity test results showed that all questionnaire items were valid, while the reliability test demonstrated good internal consistency with Cronbach’s alpha values greater than 0.70 for all variables..Data analysis was carried out bivariately using the chi-square test and multivariately using multiple logistic regression. The results of multiple logistic regression showed that the most dominant factor was the leadership variable with a p-value of 0.000 and an OR value of 153.415. The conclusion is that there is a relationship between leadership and motivation variables and the quality of nursing services in inpatient care at Pelabuhan Jakarta Hospital.